Evaluation of antinociceptive and anti-inflammatory activities of clove (Syzygium aromaticum) in vivo - Rasool, Entissar Mansour Abdul; Saleh, Abbas Najm Aldin; Al-khafaji, Mayada; Akool, Al Salihi Karima; Kadum, Hana (International Journal of Innovative Research and Scientific Studies, 2025)
Syzgium aromaticum, commonly known as clove, is a type of spice. It has an active substance called eugenol, which has significant pharmacological characteristics such as antipyretic, anesthetic, antioxidant, antibacterial, neuroprotective, and hypolipidemic properties. This study aimed to extract the eugenol oil from clove and evaluate its potential antinociceptive and anti-inflammatory activities. Eugenol was extracted from clove using direct steam distillation and chemical methods. Thin-layer chromatography and 1H NMR spectroscopy were used to identify the extract as eugenol. Eugenol was evaluated in vivo in mice using a hot plate test and carrageenan-induced paw edema for analgesic and anti-inflammatory activities, respectively. The percentages of maximal possible effect (MPE) in the hot plate test were 4.69±0.7, 3.35±0.5, and 3.34±0.6 seconds for G1, G2, and G3, respectively. Significant results were observed at P<0.05 and p<0.001 between G2 & G3, and G1, respectively, using repeated ANOVA test analysis. The extracted eugenol oil also revealed a reduction of 51.8% (p<0.05) in the mouse paw edema induced by carrageenan in comparison to indomethacin, which showed a reduction of 73.5% (p<0.01). In conclusion, the results of the current study support the potential analgesic and anti-inflammatory effects of eugenol oil and reinforce the traditional concept regarding various pharmacological activities of clove.